Unravelling adjustment mechanisms : adjustment of German expatriates to intercultural interactions, work, and living conditions in the People’s Republic of China - Angelika Zimmermann; David Holman; Paul Sparrow (2003)
Expatriate adjustment has been a prominent theme in international management research. Nevertheless, the mechanisms of adjustment have rarely been investigated. This paper addresses the issue by introducing a conceptual framework, which integrates the theoretical notion of adjustment ‘modes’ used in expatriation research with empirical descriptions of adjustment behaviours from the literature on intercultural management. The paper further reports on a qualitative, in-depth study of German expatriates in the People’s Republic of China. Participants detailed the differences they perceived in the new environment, as well as ways of adjusting to them. These included changes of expatriates’ norms of interaction, the implemention of new working methods in the Chinese workplace, and the acquisition of new living habits. Perceived environmental conditions and adjustment behaviours were contingent upon a number of factors, such as education and job level of Chinese colleagues. Conclusions are drawn and implications for organisational practice and future research are made.